PENINGKATAN KREATIVITAS MELALUI PENDEKATAN BRAIN BASED LEARNING - KUSUMAWARDANI, RATIH (Jurnal Pendidikan Usia Dini, 2015)
Abstract: The objective of this research was (1) to understand the enhancement of creativity after the Brain Based Learning Approach was implemented; and (2) to understand the implementation process of Brain Based Learning Approach in enhancing creativity.The research used two cycles action research method. Data were collected through participant observation using interview, observation, and recording, analyzed through data reduction, data display, and verification. Research finding showed that (1) the creatvity of seven children from kindergarten A in pre assessment was 11,61% and increased to 48,21% at the end of cycle 2; and (2) Brain Based Learning Approach has been succesfully enhancing creativity through seven stages and three elements of learning appropriate with the natural work of human brain. It was showed that the creativity of Kindergarten A Children in PAUD Izzati Serang Banten has enhanced 36,61% through implementing Brain Based Learning Approach. Keywords: creativity, Brain Based Learning approach, Kindergarten A children